Evaluation of nutrient parameters of selected African accessions of Bambara groundnut (Vigna subterranea (L.) verdc.) - Atoyebi, J.O.; Osilesi, O.; Adebawo, O.; Abberton, Michael T. (Science and Education Publishing Co., Ltd., 2017)
Developing countries, especially in Africa are facing challenges of malnourished conditions and food insecurity generally. Nutrients, being components of food ingredient required for survival, normal body function and satisfying the physiological and dietary requirements of the body metabolism [38]. Hence, for meaningful growth and developments in man, the type and amount of nutrients intake and its rate of absorption or level is crucial. However, much emphases and consumption pattern in Africa had been on common or routine food crops like rice, common beans, cassava, maize e.t.c., resulting in the reduced utilisation of other plant species, termed neglected and under-utilised species (NUS), like Bambara groundnut. Selected accessions of Bambara groundnut (Vigna subterranea (L.) Verdc), assembled at the International Institute of Tropical Agriculture, IITA, Ibadan, Nigeria were analysed for important nutrients parameters including moisture content, carbohydrate, protein, crude fibre, total sugar, fat, starch, ash and minerals, based on standard and established protocols at the Crop Utilisation laboratory, IITA, Ibadan, Nigeria. Moreso, samples were sent to the South African grain laboratory, the Willows, South Africa, for the determination of free and essential amino acids using HPLC and UPLC conditions. Results revealed that accessions TVSu – 1235, TVSu – 1231, TVSu – 1205, TVSu -729 and TVSu – 1824 could be regarded as high nutrients varieties, while TVSu – 1744, TVSu – 553 and TVSu - 922 are medium nutrients type, while the remaining accessions falls below the medium nutrient range, among these lines of Bambara groundnut evaluated. The protein values has a range of 15.88 ± 0.005 g / 100 g for TVSu – 1202 to 24.91 ± 0.011 g / 100 g for TVSu – 1231; while their carbohydrate content ranges from 42.77 ± 0.001 g / 100 g for TVSu – 1202 to 62.76 ± 0.223 g / 100 g for TVSu – 1744.